1D kinetic analysis and 3D multi-channel modeling of plate-type monolithic catalysts for a Selective Catalytic Reduction process. (October 2017) - Yu, Cong; Zhang, Bei; Fan, Wei; Ren, Shaojun; Li, Shuzhou; Jiang, Xiaoming; Si, Fengqi
Abstract: A comprehensive experimental and modeling method for plate-type Selective Catalytic Reduction (SCR) catalyst is presented. The analysis of mass transfer limitation was first conducted to determine the condition of the kinetic experiments, then the intrinsic kinetic parameters of SCR reaction were estimated from the kinetic experimental data using genetic algorithm. Compared to honeycomb catalyst, plate-type catalyst was coated on a supporting metal mesh. In this respect, a SCR multi-channel model was built with a correction factor of intrinsic reaction rate. Also, different diffusion coefficients in gas channels and catalyst layers were introduced. This model was validated by the experiments over a micro-scale reactor.